-90+-9k=-243

Simple and best practice solution for -90+-9k=-243 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -90+-9k=-243 equation:


Simplifying
-90 + -9k = -243

Solving
-90 + -9k = -243

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '90' to each side of the equation.
-90 + 90 + -9k = -243 + 90

Combine like terms: -90 + 90 = 0
0 + -9k = -243 + 90
-9k = -243 + 90

Combine like terms: -243 + 90 = -153
-9k = -153

Divide each side by '-9'.
k = 17

Simplifying
k = 17

See similar equations:

| 2(6x-8)=8 | | 116+28(b)=340 | | 5m-(2m+3)=5m+3(m-4) | | 9x-4-6x=2x+26 | | 8x+x+(x+10)=70 | | 14x-17y=65 | | 27ab+8a= | | -3(6+5x)=-78 | | 48*3c=7c | | log[9]x+log[9](x+8)=0 | | 10+2x=7x+40 | | 2x-5(3)=(x-2) | | 2x+5=14+2x | | -4x+10=3x-74 | | 5x+4-2x=4x-3 | | x-4y=25 | | -2x+8=x+14 | | 5x-3(2x-6)= | | X+16+x+x+29=180 | | 5x^2+40x+125=0 | | y^2+12y+8x+60=0 | | x+9.1=16.6 | | 3x^2+15x-61=0 | | -5(-4+9)-8v=6(v-6)-7 | | -4x-8=2x+40 | | -2.46x-15=-12.54 | | 9x-19=6x+20 | | 2+5x+4x=-7 | | 46.0365=7.3x+46 | | x+23+2x-27=180 | | -1x+11=-2.4+1x | | x-1+4x=39 |

Equations solver categories